Region-based shape control for multi-robot systems - Hou, Paul Saing. (2012)
Formation control of multi-robot systems has received a lot of attention from the robotic community in the past decades. While many methods have been proposed, the positions of the robots or relative positions between robots in the formation must be defined in order for the robots to form a specific shape. Therefore, as the number of robots increases, it becomes more difficult to specify the positions for all the robots. Hence, the existing control methods are not suitable to control a large group of robots to form a specific shape. The purpose of this thesis is to propose a control method for a large group of robots to form